IL28B polymorphism correlates with active hepatitis in patients with HBeAg-negative chronic hepatitis B. - I-Cheng Lee; Chen-Hao Lin; Yi-Hsiang Huang; Teh-Ia Huo; Chien-Wei Su; Ming-Chih Hou; Hui-Chun Huang; Kuei-Chuan Lee; Che-Chang Chan; Ming-Wei Lin; Han-Chieh Lin; Shou-Dong Lee (PLoS ONE, 2013)
BACKGROUND AIMS:The clinical relevance of single nucleotide polymorphisms (SNPs) near the IL28B gene is controversial in patients with hepatitis B virus (HBV) infection. This study aimed to investigate the role of viral and host factors, including IL28B genotypes, in the natural course of chronic hepatitis B (CHB). METHODS:The study enrolled consecutive 115 treatment-naive CHB patients. HBV viral loads, genotypes, precore and basal core promotor mutations, serum hepatitis B surface antigen (HBsAg) and interferon-gamma inducible protein 10 (IP-10) levels as well as four SNPs of IL28B were determined. Serial alanine transaminase (ALT) levels in the previous one year before enrollment at an interval of three months were recorded. Factors associated with active hepatitis, defined as persistent ALT >2× upper limit of normal (ULN) or a peak ALT level >5× ULN, were evaluated. RESULTS:The prevalence of rs8105790 TT, rs12979860 CC, rs8099917 TT, and rs10853728 CC genotypes were 88.3%, 87.4%, 88.4% and 70.9%, respectively. In HBeAg-positive patients (n = 48), HBV viral load correlated with active hepatitis, while in HBeAg-negative patients (n = 67), rs10853728 CC genotype (p = 0.032) and a trend of higher IP-10 levels (p = 0.092) were associated with active hepatitis. In multivariate analysis, high viral load (HBV DNA >10(8) IU/mL, p = 0.042, odds ratio = 3.946) was significantly associated with HBeAg-positive hepatitis, whereas rs10853728 CC genotype (p = 0.019, odds ratio = 3.927) was the only independent factor associated with active hepatitis in HBeAg-negative population. CONCLUSIONS:HBV viral load and IL28B rs10853728 CC genotype correlated with hepatitis activity in HBeAg-positive and HBeAg-negative CHB, respectively. Both viral and host factors play roles in disease activity during different phases of CHB.